2013
DOI: 10.1097/brs.0b013e31829fc56f
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Bone Morphogenetic Protein-2-Augmented Transforaminal Lumbar Interbody Fusion for the Treatment of Chronic Low Back Pain Secondary to the Homogeneous Diagnosis of Discogenic Pain Syndrome

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Five studies [26, 27, 29, 36, 37] included data on the rate of return to work after OS surgery. Berg et al [36] reported on a clinical RCT comparing total disc replacement (TDR) and instrumented lumbar spinal fusion (i.e., PLF or PLIF) in Sweden.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies [26, 27, 29, 36, 37] included data on the rate of return to work after OS surgery. Berg et al [36] reported on a clinical RCT comparing total disc replacement (TDR) and instrumented lumbar spinal fusion (i.e., PLF or PLIF) in Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…Corenman et al [37] presented a small, 2 year retrospective observational study, where data were collected from a return to work questionnaire. The study found that 84.4% (27/32) of the cohort were able to return to the same job as before the surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proteins have been reported as good replacements of autologous bone graft in non-union, spine fusion and bone defect (Corenman et al, 2013;Moghaddam-Alvandi et al, 2012). However, rhBMP-2 is also known to cause soft tissue swelling, osteolysis and retrograde ejaculation by inducing ectopic bone formation, seroma formation and inflammation (Carragee et al, 2011;Helgeson et al, 2011;Smoljanovic et al, 2011).…”
Section: Introductionmentioning
confidence: 96%